Nutritional Studies on the Bioavailability of Iron From Cereals and Pulses - Jainita M Mehta (Department of Home Science, College of Horticulture, 1998)
Nutritional studies to evaluate the bioavailability of iron was conducted among three selected cereals i.e., rice, wheat and ragi and six pulses i.e., Bengal gram, green gram, black gram, horse gram, cowpea and soya bean. The results of the study indicated that among cereals though the total iron was maximum for ragi but the absolute available iron was less mainly due to its high fibre and tannin content. Its availability was considerably improved by germinating ragi for 48 hours when cereals were processed, refined wheat flour had the maximum iron availability owing to the reduction of fibre and phytic acid content on refining, while ragi had the least iron availability. Among pulses the total and absolute available iron was maximum for bengal gram and soya bean and least for black gram which was found to be high in phytin phosphorus and tannin content. The total and absolute available iron increased on dehulling pulses except in the case of soyabean. This increase in iron was mainly due to the fact that most of the tannins reside in the seed coat of pulses which are removed on dehulling. A further increase in the iron content was observed on germinating the pulses due to the break down of antinutritional factors during germination. A slight increase in the absolute available iron of fermented and unfermented idli batter was observed which became more available on cooking by steaming. On germinating and roasting ragi almost a four to six fold increase in the absolute available iron was observed while in pulse the absolute available iron almost doubled on roasting bengal gram while a ten to fifteen fold increase was